The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00170-014-6151-6
|View full text |Cite
|
Sign up to set email alerts
|

A synthetical stability method for cutting parameter optimization to assure surface location accuracy in flexible part milling

Abstract: Flexible parts are widely used in the aeronautic and power industries which have high machining accuracy requirement. However, the flexible part is apt to vibrate in cutting processes due to its low structure stiffness and damping. Accurate approximation of cutting stability boundary of flexible part is difficult, because traditional stability analysis simplifies the complex dynamic system and some parameters still have large vibrations and can cause bad surface accuracy even when they are predicted to be loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Combine Eqs. (9) and (23), and the state transition relationship on a tooth passing period interval can be formulated as follows: …”
Section: Approximation Of Second Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…Combine Eqs. (9) and (23), and the state transition relationship on a tooth passing period interval can be formulated as follows: …”
Section: Approximation Of Second Ordermentioning
confidence: 99%
“…In the early days, the time domain methods [6][7][8] are used for the simulations of chatter vibration in the cutting process, and they are quite suitable for complex situations, such as in the case of thin-walled part milling [9] and variable pitch end milling [10]. To improve the computation accuracy and efficiency of stability, much effort has been devoted to acquire the stability lobe diagrams analytically or semi-analytically.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Schmitz's team proposed methods to predict the SLE in time and frequency domain, and pointed out that the SLE was dependent on the machining parameters [21], [22]. As the SLE determines the geometric accuracy of the workpiece, it should be discussed in the machining parameters optimization [23]. Zhang et al [24] had emphasized uncertain parameters in milling process and established a formulation for obtaining the robust minimum SLE and maximum spindle speed.…”
Section: Introductionmentioning
confidence: 99%
“…Thevenot et al [33] reported a three dimension lobes construction method and applied it to thin-walled structure milling. Zhang et al [34] proposed a synthetical stability analysis method for flexible part milling, in this method the regenerative dynamic excitation and steady periodical excitation are simultaneously considered.…”
Section: Introductionmentioning
confidence: 99%